A Proposal for the Demarcation of Theory and Knowledge: Of Language‐dependent and Language‐independent Reality. (24th January 2020) - Kampen, Jarl K.
Abstract: Research communication in interdisciplinary research projects requires a way of demarcation of theory and knowledge that is easy to communicate, is inconsequential for the framework of concepts, results, and procedures within existing scientific disciplines, and abstains from trying to resolve the dispute between (neo)positivists and constructivists. A simple way of demarcation starts from the notion of language‐independent and language‐dependent reality. Currently, what passes for knowledge ("news") and myth ("fake news") depends, besides on sheer volume and frequency of the messages, increasingly on the internal consistency of (computer) language‐dependent reality and decreasingly on language‐independent reality. All language is instruction, and knowledge is to know which instructions (that is, theory) are predictive of a result, state, or situation in language‐independent reality. Any theory that doesn't reduce outcome space, or contains one or more empirically/physically impossible instructions, or produces wrong predictions, or falls short of demonstration is not knowledge.